2000
DOI: 10.1139/f00-085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inorganic nitrogen cycling on the δ15N of Lake Ontario biota

Abstract: The seasonal variability in the δ15N of biota at the base of the pelagic food chain in Lake Ontario was studied during the period 1995-1997. Strong seasonal patterns were observed in the δ15N of dissolved inorganic nitrogen, different size fractions of particulate organic matter, and zooplankton split into size fractions of 110-210, 210-295, and >295 µm. Similar patterns were reflected in the δ15N of individual species: Diacyclops thomasi, Bosmina longirostris, Daphnia spp., and calanoid copepods. The seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Individual zooplankton species exhibit large seasonal variation in ␦ 15 N (Graham 1997;Leggett et al 2000). How do we account for this large variation in our estimates of fish trophic position and trophic variation using ␦ 15 N?…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual zooplankton species exhibit large seasonal variation in ␦ 15 N (Graham 1997;Leggett et al 2000). How do we account for this large variation in our estimates of fish trophic position and trophic variation using ␦ 15 N?…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Different zooplankton taxa have unique isotopic signatures (Meili et al 1996;Matthews and Mazumder 2003) and can exhibit distinct seasonal patterns of ␦ 15 N (Graham 1997;Leggett et al 2000;Grey et al 2001; Fig. 2).…”
Section: Specific Taxa or Bulk Size Fractions For ␦mentioning
confidence: 99%
See 1 more Smart Citation
“… A schematic illustration of the measured δ 15 N ranges of particulate organic matter (PON), NH4+ and NO3, and predicted values of excess N 2 formed in denitrification, based of the studies on Lake Lugano,25 Jyväsjärvi 22 and Ontario 26 surface waters.…”
mentioning
confidence: 99%
“…Uncertainties-An additional process that may contribute to the asymptotic trend that we observed is uptake fractionation of inorganic N (Leggett et al 2000). Marine and lab studies have demonstrated that d 15 N of phytoplankton will asymptote as the availability of surface water NO { 3 increases (Altabet and Francois 1994;Sigman et al 1999;Altabet 2006).…”
Section: Discussionmentioning
confidence: 92%